The use of nanoparticles for targeted drug delivery in non-small cell lung cancer - Holder, Jessica E.; Ferguson, Christopher; Oliveira, Elisabete; Lodeiro, Carlos; Trim, Carol M.; Byrne, Lee J.; Bertolo, Emilia; Wilson, Cornelia M. (Frontiers in Oncology, 2023)
Lung cancer is a global health problem affecting millions of people each year. Non-small cell lung cancer (NSCLC) is the most common form of lung cancer with various conventional treatment available in the clinic. Application of these treatments alone often results in high rates of cancer reoccurrence and metastasis. In addition, they can cause damage to healthy tissues, resulting in many adverse effects. Nanotechnology has emerged as a modality for the treatment of cancer. When used in combination with nanoparticles, it is possible to improve the pharmacokinetic and pharmacodynamic profiles of pre-existing drugs used in cancer treatment. Nanoparticles have physiochemical properties such as small size which allowing passage through challenging areas of the body, and large surface area allows for higher doses of drugs to be brought to the tumor site. Nanoparticles can be functionalized which involves modifying the surface chemistry of the particles and allows for the conjugation of ligands (small molecules, antibodies, and peptides). Ligands can be chosen for their ability to target components that are specific to or are upregulated in cancer cells, such as targeting receptors on the tumor surface that are highly expressed in the cancer. This ability to precisely target the tumor can improve the efficacy of drugs and decrease toxic side effects. This review will discuss approaches used for targeting drugs to tumors using nanoparticles, provide examples of how this has been applied in the clinic and highlight future prospects for this technology.